Management of Vesicouterine Fistulae during "Fistulae Surgical Caravan" in Cote D'ivoire - Djanhan, L.E.; Dia, J.M.; Menin, M.M.; Kouamé, B.; Bohoussou, E.; Samaké, Y.; Kouakou, K.P.; Doumbia, Y. (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims : To describe the epidemiological, clinical and therapeutic characteristics of patients treated for vesico-uterine fistula. Methods : This was a case series of 34 patients prospectively collected for descriptive purposes. They were treated for Vesico-uterine fistulae during "fistulas surgical caravans" from 1st January 2012 to 31st December 2016. Results :Vesico-uterine fistulae represented 2.1% of all treated urogenital fistulae. At the time of fistula occurrence, the average age of the patients was 33.3 years, and the majority were illiterate (88.2%), lived in rural areas and were unemployed (73.5%). All the fistulae were associated to childbirth, the majority of which took place on a scarred uterus (67.6%). And this childbirth responsible for the fistula was a delivery done by caesarean section in 97.7% of cases. Average duration of the fistula before management was 6 years. Finally, all the patients were operated by the same surgical technique, made by abdominal extra peritoneal transvesical way. The successful first repair rate was 97.1% in 33 patients. The only case of failure was successfully cured using surgical another technique in a second attempt. Conclusion: The vesicouterine fistulae were rare, were mostly associated to previous uterus surgical history and the successful rate is almost 100%.